How attitude, perceived savings, price discount affect, perceived food quality shapes purchase intentions of Menu Rahmah - Wan Nawang, Wan Rasyidah; Zainudin, Amirul Amri; Hashim, Nor Haziah (Universiti Teknologi Mara Selangor, 2025)
Malaysians are still dealing with the COVID-19 pandemic’s aftermath, despite its recovery. Compounded by the slowdown in the economy, many Malaysians are struggling to afford even the most basic meals. The Malaysian government has introduced Menu Rahmah, a pricediscounted meal option, as a response to the current economic crisis, offering an ideal choice for Malaysians in need. The study aims to explore Malaysians’ purchase intentions toward Menu Rahmah by extending the Theory of Planned Behaviour (TPB). The data was gathered from 283 Malaysians through an online survey questionnaire. A partial least square structural equation modelling (PLS-SEM) was used to analyse the relationships between the study variables. The study’s empirical results indicate that attitude, perceived savings, and price discounts affect significantly influence Malaysians’ purchase intention of Menu Rahmah, while perceived food quality does not. This study contributes to the growing literature on TPB and consumer behaviour in discounted products. Additionally, the Malaysian government’s Menu Rahmah initiative is a commendable effort to assist struggling Malaysians. By analysing the impact of attitude, perceived savings, and price discounts on Malaysians’ purchase intentions, the government and its Menu Rahmah operators can encourage more consumption as an alternative.